Multiple myeloma with primary systemic amyloidosis affecting cutaneous, gastro intestinal and cardio-vascular system - A. S., Mohammed Feros; Shanmugam, Lokesh (International Journal of Advances in Medicine, 2019)
Amyloidosis refers to a group of disorders characterized by extracellular deposition of protein fibrils. Primary systemic amyloidosis is commonly due to an underlying plasma cell dyscrasia. Infiltrative amyloid cardiomyopathy is a rare cause of predominantly diastolic myocardial disease. Restrictive cardiomyopathy is the main finding in cardiac amyloidosis and results from the replacement of normal myocardial contractile elements by infiltration and interstitial deposits of amyloid, leading to alterations in cellular metabolism, calcium transport, receptor regulation, and cellular edema. Injury can also occur from circulating light chains in the absence of amyloid fibril formation. Cardiac amyloidosis should be considered in any patient presenting with congestive heart failure, preserved systolic function, and a discrepancy between a low QRS voltage on electrocardiography and an apparent left ventricular hypertrophy on sonogram. The pattern of left ventricular diastolic dysfunction changes during the course of amyloidosis and the classically described restrictive physiology occurs only in advanced stages of the disease. This is a case report where an unusual extensive cutaneous and cardiac involvement provided the sign of widespread systemic deposition of amyloid protein which eventually led to the diagnosis of multiple myeloma.